Pengaruh CR, DAR, dan TATO terhadap ROA pada Perusahaan Subsektor Minyak, Gas, dan Batu Bara yang Terdaftar di ISSI Periode 2022-2024 - Sasa Aprilia Amanda; Zulfa Khairina Batubara (Lembaga Pengembangan Kinerja Dosen, 2026)
This research is intended to examine the relationship between CR, DAR, and TATO and ROA in companies within the oil, gas, and coal subsector listed on the Indonesian Sharia Stock Index (ISSI) during the 2022–2024 period. The study aims to provide empirical evidence regarding the influence of financial ratios on the profitability level of companies in the energy sector, which plays an important role in the economy. The approach applied in this study is quantitative, utilizing secondary data in the form of financial position reports and company performance reports obtained from the Indonesia Stock Exchange. The sample was determined using a purposive sampling technique based on specific criteria to ensure that the data obtained were relevant to the needs of the research analysis. Data processing techniques were carried out using the multiple linear regression method, supported by statistical software to evaluate the effect of each independent variable as well as their collective influence on the dependent variable. The empirical findings indicate that CR, DAR, and TATO simultaneously have a significant effect on ROA. Partially, CR and DAR show a negative and significant relationship with ROA, while TATO shows a positive but not significant relationship. The coefficient of determination indicates that the explanatory power of the model is relatively low, suggesting that company profitability is also influenced by various other factors beyond the variables analyzed in this study.